Spearfishing and public health promotion: A cross-sectional analysis of the Hawaiʻi Behavioral Risk Factor Surveillance System Survey - Lauryn Hansen; Yan Yan Wu; Tetine Lynn Sentell; Mika Thompson; Tonya Lowery St. John; Simone Schmid; Catherine McLean Pirkle (PLoS ONE, 2025)
Spearfishing, a culturally relevant practice in many locations globally, may foster physical activity and enhance well-being by promoting social cohesion, food security, and nature connectedness, but is understudied in public health promotion and surveillance. This study measured the population-level prevalence of lifetime spearfishing engagement in Hawaiʻi and identified associated factors for public health promotion. The Hawaiian Islands present an ideal setting for such activities due to its central Pacific location and a diverse population with cultural ties to spearfishing. In 2019 and 2020, lifetime spearfishing engagement was added to the Hawai’i Behavioral Risk Factor Surveillance System (N = 12,737). Prevalence ratios (PR) and 95% confidence intervals (95%CI) were estimated for spearfishing “sometimes,” “often,” or “very often” during one’s lifetime, considering sociodemographic, health behavior, and health status variables. A quarter of respondents statewide reported engagement, with higher rates amongst men (41%), Native Hawaiians (43%), other Pacific Islanders (36%), American Indian or Alaskan Native (32%), and rural island residents of Lānaʻi (51%) and Molokaʻi (43%). All age groups reported similar lifetime engagement. After statistical adjustment, those with a high school diploma or less were significantly more likely to have engaged in spearfishing than those with higher education. Spearfishing engagement was also associated with a higher likelihood of meeting physical activity guidelines (PR 1.45 95%CI 1.29-1.63). There is widespread lifelong engagement in spearfishing in Hawaiʻi, especially among Indigenous and rural populations. Supporting culturally relevant activities, such as spearfishing, is a strength-based approach to health promotion with global relevance, including encouraging physical activity.